ENT : AN INTRODUCTION AND PRACTICAL GUIDE - Tysome, James Russell; Kanegaonkar, Rahul Govind (CRC Press, 2023)
"The third edition of ENT: An Introduction and Practical Guide provides an essential introduction to the clinical examination, treatment options and surgical procedures within ENT. It encompasses the most frequently encountered conditions in the emergency setting, on the ward and in the outpatient clinic. Updated to include new content on implantation surgery for hearing loss. It also incorporates significant changes in the coverage of indications for surgery, patient assessment and management, and surgical techniques. The subjects of dizziness and vertigo have also been updated to include novel interventions. With its highly practical approach and step-by-step guidance, this book will be invaluable for all surgical trainees studying for higher postgraduate examinations in ENT, as well as an essential guide for otorhinolaryngologists, primary care practitioners and specialist ENT nurses in the early years of training"--